Casein Kinase 1 Delta Regulates Cell Proliferation, Response to Chemotherapy and Migration in Human Ovarian Cancer Cells - Mazzoldi, Elena Laura; Pastò, Anna; Ceppelli, Elisa; Pilotto, Giorgia; Barbieri, Vito; Amadori, Alberto; Pavan, Simona (Frontiers in Oncology, 2019)
Casein kinase 1 delta (CK1δ) has a tumor-promoting role in different cancers and it is genetically amplified in a portion of human epithelial ovarian cancer (EOC). CK1δ is involved in pleiotropic cellular functions such as cell proliferation, DNA damage, and migration. We specifically knocked down CK1δ by short hairpin RNA (shRNA) in human ovarian cancer cells and we performed proliferation, chemosensitivity, as well as in vitro and in vivo migration assays. CK1δ knocked-down cells displayed reduced proliferation capability both in vitro and in vivo. Nonetheless, these cells were sensitized to the first line chemotherapeutic agent carboplatin (CPT), and this observation could be associated to reduced expression levels of p21(Cip1/Waf1), involved in DNA damage response, and the anti-apoptotic X-linked inhibitor of apoptosis protein (XIAP). Moreover, CK1δ knocked-down cells were affected in their migratory and lung homing capability, even if in opposite ways, i.e. IGROV1, SKOV3 and MES-OV lost, while OVCAR3 gained motility potential. The results suggest CK1δ as a potential exploitable target for pharmacological EOC treatment, but they also advise further investigation of its role in cell migration.